2016
DOI: 10.3892/ijmm.2016.2631
|View full text |Cite
|
Sign up to set email alerts
|

TGF-β1, in association with the increased expression of connective tissue growth factor, induce the hypertrophy of the ligamentum flavum through the p38 MAPK pathway

Abstract: Hypertrophy of the ligamentum flavum (LF) is one of the key pathomechanisms of lumbar spinal stenosis (LSS). Transforming growth factor (TGF)-β1 is abundantly expressed in hypertrophied degenerative LF tissues from LSS. However, the molecular mechanisms underling the association between TGF-β1 and LF hypertrophy have not yet been fully elucidated. In this study, we investigated the important role of the mitogen-activated protein kinase (MAPK) pathway in the pathogenesis of LSS by analyzing the expression of co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
31
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(34 citation statements)
references
References 35 publications
0
31
0
3
Order By: Relevance
“…Research on the pathophysiology of LFH has been of great interest to spine specialists, and the majority of specialists have suggested that tissue inflammation, angiogenesis, and fibrosis lead to LFH . Although the development of LFH cannot be described by a single pathway or a single biomechanical change, the relationships between LFH and several key factors, including transforming growth factor‐β1 (TGF‐β1), angiopoietin‐like protein 2 (ANGPTL2), vascular endothelial growth factor (VEGF), and several other cytokines have been investigated . It is widely known that among these cytokines, TGF‐β1 is the main component of LFH that leads to LSCS.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Research on the pathophysiology of LFH has been of great interest to spine specialists, and the majority of specialists have suggested that tissue inflammation, angiogenesis, and fibrosis lead to LFH . Although the development of LFH cannot be described by a single pathway or a single biomechanical change, the relationships between LFH and several key factors, including transforming growth factor‐β1 (TGF‐β1), angiopoietin‐like protein 2 (ANGPTL2), vascular endothelial growth factor (VEGF), and several other cytokines have been investigated . It is widely known that among these cytokines, TGF‐β1 is the main component of LFH that leads to LSCS.…”
mentioning
confidence: 99%
“…It is widely known that among these cytokines, TGF‐β1 is the main component of LFH that leads to LSCS. Several studies have elucidated the key links of TGF‐β to inflammation, angiogenesis, extracellular matrix (ECM) regulation, and myofibroblast transdifferentiation leading to LFH. However, convincing evidence is still lacking regarding whether inhibition of the TGF‐β pathway can actually prevent LFH.…”
mentioning
confidence: 99%
“…Some studies suggested that chronic inflammation induced by mechanical stress was a vital impact factor for HLF [11,12]. It is believed that when suffering from increased mechanical stress, the ligamentum flavum is constantly damaged, causing a local release of inflammationrelated factors, such as TNF-α, TGF-b1, IL-1 and IL-6, which can stimulate LF fibrosis and contribute to the pathological process of HLF [12,[33][34][35][36]. Although inflammatory factors are believed to play a crucial role in HLF [5,11,[37][38][39][40], the molecular basis for LF tissue fibrosis remains unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Об аналогичных наблюдениях в отношении гипертрофированной желтой связки сообщили [24], фибробластов оболочки глаза [25].…”
Section: марк как потенциальные регуляторы роста соединительной тканиunclassified